A Comparative Psychoanalytic Reading of Confessional Poetry: John Berryman and Kamala Das - CHOWDHURY, AFSANA (International Journal of Language and Literary Studies, 2026)
This study presents a comparative analysis of confessional poetry through the works of John Berryman and Kamala Das, focusing on how the confessional mode functions differently in Western and Indian cultural contexts. The confessional poetry genre, popular in the middle of the twentieth century, is often linked to extreme self-disclosure, personal trauma, and inner struggle, especially when it comes to the poems of Western poets. But this paper will argue that this definition is inadequate when it comes to explaining the various cultural interpretations of the concept of confession in non-Western literature. The study employs Freudian theories of the unconscious, guilt, repression, desire and trauma which is done using a psychoanalytic approach in analyzing Berryman “Dream Songs” and “Book of Sonnets”. Through his poetry a very inward- looking confessional style can be observed that is influenced by the conflict in his mind that had been left unresolved, his emotional instability, and his self-destructive tendencies. Kamala Das poetry, on the contrary, is also explained in the context of the collective unconscious, as formulated by Carl Jung. Though her poems are very personal in the tone, it goes beyond the personal to collectively reflect the emotional and psyche reality of an Indian woman, as she lived in the patriarchal and postcolonial system. By studying the text carefully, the study demonstrates that at the same time when Berryman uses confessional poetry to focus on the personal experience of suffering and inner breakdown, Das converts personal confession into an effective cultural critique and feminism. Her poetic “I” transforms into a shared voice that breaks social taboos, gender inequality and emotional restraint. Through the comparison of the two poets, the paper reveals the adaptability of the confessional poetry and outlines the necessity of culturally aware psychoanalytic approaches that take into account gender, society and its historical times. In the end, the paper will show that confessions poetry may be used as a way of an individual psychological resistance and as a way of communal protest and societal change.